The Ayios Vasileios Survey Project (Laconia, Greece): questions, aims and methods - Voutsaki, Sofia; Wiersma, Corien; de Neef, Wieke; Vasilogamvrou, Adamantia (Journal of Greek Archaeology, 2019)
This article presents the research design, i.e. the main aims, questions and methods of the Ayios Vasileios Survey Project. This ongoing project combines field walking, geophysical prospection and ethnographic interviews in order to place more firmly the Mycenaean Palatial Complex of Ayios Vasileios (Laconia, Greece) in its physical, regional and historical context.